Improvement of pulmonary arterial compliance by pulmonary vasodilator in pulmonary hypertension from combined pulmonary fibrosis and emphysema. (2019) - Kusaka, Kei; Morio, Yoshiteru; Kimura, Yuya; Takeda, Keita; Kawashima, Masahiro; Masuda, Kimihiko; Matsui, Hirotoshi
Abstract: Combined pulmonary fibrosis and emphysema (CPFE) is a common but under-recognized syndrome characterized with distinct profiles of both pulmonary fibrosis and emphysema. Pulmonary hypertension (PH) is particularly prone to develop as a common complication, leading to exercise limitation and worse prognosis of CPFE. Although the therapy of patients with PH from CPFE cannot be endorsed, an individual treatment may be considerable when accompanying severe PH. We report a case of a 71-year-old male with PH from CPFE, who improved pulmonary arterial compliance (PAC) and exercise capacity in response to pulmonary vasodilator.